Analisis Kesesuaian Kriteria Standar Kamar Hotel Bintang 3 di Sun Hotel Madiun Berdasarkan PERMENPAREKRAF No. PM.53/HM.001/MPEK/2013 Analysis of Compliance with Three-Star Hotel Room Standard Criteria at Sun Hotel Madiun Based on the Regulation of the Mi - Wulandari, Saktiana; Handayani, Lutfi; Lasally, Adesty; Arifin, Samsul; Erryawan, Ervin (EBBANK, 2025)
This research aims to analyze the compliance of Sun Hotel Madiun’s room standards with the three-star hotel criteria based on the Regulation of the Minister of Tourism and Creative Economy of the Republic of Indonesia No. PM.53/HM.001/MPEK/2013. The study employed a descriptive qualitative method through field observations, documentation, and comparison with government regulations. The findings indicate that most of the room standards at Sun Hotel Madiun meet both mandatory and non-mandatory criteria, particularly in terms of product, service, and management aspects. However, several shortcomings were identified, including the absence of special rooms for guests with disabilities, limited availability of hair dryers, and restricted in-room communication services. In terms of management, the organizational structure and SOPs are well-implemented, but staff foreign language training and Corporate Social Responsibility (CSR) programs require improvement. The study concludes that Sun Hotel Madiun generally meets the standards of a three-star hotel, yet continuous improvements are necessary to enhance service quality, accessibility, and competitiveness in the hospitality industry.